Pengaruh modal kerja dan perputaran persediaan terhadap laba bersih pada perusahaan sektor kesehatan yang terdaftar di bursa efek indonesia (BEI) - Husniati, Adilah; Ridwan, Rizky; Khodijah, Amalia Siti (Universitas Widyatama, 2026)
The study was conducted to analyze the effect of working capital and inventory turnover on net profit. A quantitative approach was applied using secondary data in the form of financial statements. The population included health sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. A purposive sampling method was applied, resulting in a sample of 25 companies. Data analysis was performed by applying panel data regression using EViews software version 13. Based on the test results, working capital had a positive and significant effect on net profit, while inventory turnover had a negative and significant effect on net profit. Simultaneously, these two independent variables significantly affect net profit in healthcare companies. The findings of this study are expected to serve as a reference for companies in managing working capital and inventory more efficiently to increase profitability.